2021
DOI: 10.1186/s12879-021-06150-3
|View full text |Cite
|
Sign up to set email alerts
|

Silent existence of eosinopenia in sepsis: a systematic review and meta-analysis

Abstract: Background Sepsis is a life-threatening and time-critical medical emergency; therefore, the early diagnosis of sepsis is essential to timely treatment and favorable outcomes for patients susceptible to sepsis. Eosinopenia has been identified as a potential biomarker of sepsis in the past decade. However, its clinical application progress is slow and its recognition is low. Recent studies have again focused on the potential association between Eosinopenia and severe infections. This study analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…In this study, all cases of deep abscesses and sepsis secondary to skin infections appeared in the eosinopenia group, which was consistent with previous research that demonstrated eosinophils may be a marker during bacterial infections [ 3 , 4 ]. Thus, we can make better diagnoses and reduce antibiotic abuse in adult varicella patients with eosinophils.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, all cases of deep abscesses and sepsis secondary to skin infections appeared in the eosinopenia group, which was consistent with previous research that demonstrated eosinophils may be a marker during bacterial infections [ 3 , 4 ]. Thus, we can make better diagnoses and reduce antibiotic abuse in adult varicella patients with eosinophils.…”
Section: Discussionsupporting
confidence: 92%
“…Eosinophils were considered as protective factors in respiratory viruses infections in recent studies [3][4][5][6]. It has been demonstrated that the eosinophil antiviral response depends on the inclusion and production of molecules with antiviral activity, including RNA enzymes and active nitrogen species, the participation of eosinophils in adaptive immunity because they can act as antigen-presenting cells, and the eosinophil extracellular traps [6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis by Lin et al, including a total of 3.842 patients, showed that eosinopenia has a high incidence in sepsis, but it is not superior to conventional biomarkers for diagnosing sepsis, such as C reactive protein (CRP) and procalcitonin (PCT) [52]. It should be considered that the studies currently available on the accuracy of eosinopenia as a sepsis biomarker present a high heterogeneity, with sensitivity ranging from 23.2 to 92.5% and specificity from 28.57 to 91%.…”
Section: Eosinophilsmentioning
confidence: 99%
“…Shaaban et al [ 37 ] defined an optimum cut-off value of 50 cells/μL, which produced an SS, SP, and NPV of 81%, 65% and 80%, respectively. At hospital admission, ECC < 40 cells/μL is an independent prognostic factor for mortality[ 38 , 39 ]. Our study is original in assessing the usefulness of ECC for the early diagnosis of CAL.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of CRP as a biomarker for early detection of CAL has been investigated by several groups[ 19 , 25 , 39 , 41 , 42 ]. In this study, the plasma CRP level exhibited a propensity to normalize from POD3 onwards in patients without CAL (G1 and G2).…”
Section: Discussionmentioning
confidence: 99%